Integrating clients' moment‐to‐moment ratings into psychotherapy research: A novel approach. Issue 3 (31st January 2020) - Penix, Elizabeth A.; Swift, Joshua K.; Trusty, Wilson T.
Abstract: Counselling and psychotherapy researchers have considerably advanced the field's understanding of psychotherapy processes and how they relate to treatment outcomes. Despite these advances, little is known about the client's perspective of changes in psychotherapy processes that occur throughout a given session (i.e. micro‐processes). To address this gap, this article describes the novel application of methods that assess participants' moment‐to‐moment ratings to psychotherapy research. This method entails recording psychotherapy session content that clients and other potential raters (e.g. therapists, researchers) later review while simultaneously providing continuous ratings of psychotherapy processes (e.g. helpfulness, alliance). In addition, moment‐to‐moment ratings can facilitate significant events research by prompting researchers to elicit client feedback about the moments that are rated the most and least positively. However, few studies have used these methods in the context of psychotherapy research. Studies incorporating these methods may yield findings that advance psychotherapy research, training efforts and clinical practice. For example, studies may examine how the magnitude and timing of clients' moment‐to‐moment ratings of psychotherapy processes are associated with treatment outcomes, therapist ratings and physiological processes (e.g. heart rate variability). Trainee therapists and their supervisors may also use clients' moment‐to‐moment ratings to facilitate attunement to verbal and non‐verbal indicators of moments perceived more positively and negatively. Last, these methods can produce findings that are highly relevant to clinical practice, where therapists routinely navigate fluctuations in psychotherapy processes (e.g. alliance ruptures) that can be assessed using moment‐to‐moment ratings.